Manajemen Pengeluaran Pupuk dengan Sistim Untilan dari Gudang Central untuk Menunjang Aplikasi Pemupukan Yang Benar - Muhammad Sapruwan (Politeknik Kelapa Sawit Citra Widya Edukasi, 2011)
Untilan system is a system that is simple and easy to do. because it can keep the dose / size of the fertilizer, labor, facilitates activities such as facilitating the timing, methods and goals, so that when untilan system can be managed properly at the time of release of goods from the warehouse, is expected to obtain the correct application of fertilizer. And finally, can increase crop productivity. Where the expenditure management system with the expected target untilan applying the proper fertilizer application can achieve, namely, Right Dose, Right Time Right Targets How.